Analisis tentang Organisasi Manajemen Wirausaha - A. M. Rawis, Joulanda (Jurnal Aplikasi Manajemen, 2009)
Entrepreneurship is viewed as modern issue in education. There are many positive values can be taken to improve the educational organization, as self belief, high ethos, creative, innovative, etc. the first step in educational entrepreneur ship management is an effort planning. To develop the educational institution, educational leader must define a good program. Based on the program, he can organize, coordinate or control the organization.